Dormancy and germination in Talipariti elatum seeds - Montejo Valdés, Laura A.; Sánchez, Jorge A.; Muñoz, Bárbara (Botanica Complutensis, 2005)
The dormancy in fresh seeds of Talipariti elatum (Sw.) Fryxell from moist evergreen forest and secondary vegetation was determined. Structural and germinative variables of the seeds were studied, and water absorption dynamics of intact and scarified seeds was determined. In seeds from both ecosystems, the dry weight of seed coats was higher than the food storage weight. Intact seeds absorbed water but lacked the triphasic pattern of absorption shown by scarified seeds. 88% intact seeds were hydrated in contact with water, though 30% ± were scarcely hydrated (up to 30% humidity) and over 50% showed hydration values surpassing 30%. Germination in intact seeds was poor and erratic, contrary to coatless seeds. Results show that fresh seeds do not have exogenous dormancy as the only impediment for avoiding germination, but a mechanical dormancy in combination with a certain degree of seed coat impermeability to water which prevent germination.